2010
DOI: 10.1104/pp.110.169482
|View full text |Cite
|
Sign up to set email alerts
|

Three Homologous Genes Encodingsn-Glycerol-3-Phosphate Acyltransferase 4 Exhibit Different Expression Patterns and Functional Divergence inBrassica napus       

Abstract: T9C 1T4 (A.E.-M., S.S.)Brassica napus is an allotetraploid (AACC) formed from the fusion of two diploid progenitors, Brassica rapa (AA) and Brassica oleracea (CC). Polyploidy and genome-wide rearrangement during the evolution process have resulted in genes that are present as multiple homologs in the B. napus genome. In this study, three B. napus homologous genes encoding endoplasmic reticulumbound sn-glycerol-3-phosphate acyltransferase 4 (GPAT4) were identified and characterized. Although the three GPAT4 hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 56 publications
3
51
0
3
Order By: Relevance
“…agreement with the results in Arabidopsis, increases or decreases of C16/C18 leaf cutin monomers are observed after ectopic expression of a GPAT4/8 homolog from Echium pitardii in tobacco (Mañas-Fernández et al, 2010) or by silencing of GPAT4 homologs in Brassica napus (Chen et al, 2011b). Thus, for most monomers, the in vivo data coincide with in vitro enzyme specificity data.…”
Section: Sn-2-gpat Acyl Specificity As a Determinant Of Cutin/suberinsupporting
confidence: 88%
“…agreement with the results in Arabidopsis, increases or decreases of C16/C18 leaf cutin monomers are observed after ectopic expression of a GPAT4/8 homolog from Echium pitardii in tobacco (Mañas-Fernández et al, 2010) or by silencing of GPAT4 homologs in Brassica napus (Chen et al, 2011b). Thus, for most monomers, the in vivo data coincide with in vitro enzyme specificity data.…”
Section: Sn-2-gpat Acyl Specificity As a Determinant Of Cutin/suberinsupporting
confidence: 88%
“…Although the enzymatic activity of AtGPAT9 has not been directly confirmed and its physiological function is unknown, polypeptide sequence alignment, phylogenetic analysis, conserved domain analysis and gene expression data have all suggested that AtGPAT9 may play an essential role in the synthesis of membrane and storage lipids in plants (Gidda et al, 2009;Chen et al, 2011b). Expression profiling revealed that the levels and tissue-specific accumulations of AhGPAT9 transcript are distinct from those of other GPAT family members, which is consistent with the more diverged nature of the AtGPAT9 gene.…”
Section: Discussionmentioning
confidence: 99%
“…In Brassica napus, three homologous GPAT4 genes exhibited different expression patterns and distinct epigenetic features. A phenotypic rescue of a gpat4 gpat8 Arabidopsis double mutant and analysis of the gpat4 RNAi lines of B. napus suggested physiological roles of GPAT4s in cuticle formation of the rosette leaves, early flower development, pollen development, and the biosynthesis of storage lipids (Chen et al, 2011b). Two homologous GPAT genes isolated from Echium pitardii have high similarity to the AtGPAT4/8 genes of Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…Expression analysis of GPAT family members in the SlDCR-RNAi fruit revealed that only Solyc04g011600 (SlGPAT5) displayed a significantly altered expression, showing a >350-fold increase in expression compared with wild-type fruit skin ( Figure 1G; Supplemental Figure 5B). Importantly, SlGPAT4 and SlGPAT6, considered to be involved in cutin polymer formation (Yang et al, 2010;Chen et al, 2011b;Petit et al, 2016), showed no change in expression (Supplemental Figure 5).…”
Section: Silencing the Tomato Defective In Cuticular Ridges Results Imentioning
confidence: 99%